2021
DOI: 10.1111/liv.14992
|View full text |Cite
|
Sign up to set email alerts
|

Safety of direct oral anticoagulants in patients with advanced liver disease

Abstract: Background & Aims While direct oral anticoagulants (DOACs) are increasingly used in patients with liver disease, safety data especially in advanced chronic liver disease (ACLD) are limited. Methods Liver disease patients receiving DOAC treatment (ACLD: n = 104; vascular liver disease: n = 29) or vitamin K antagonists (VKA)/low‐molecular‐weight heparin (LMWH; ACLD: n = 45; vascular: n = 13) between January 2010 and September 2020 were retrospectively included. Invasive procedures and bleeding events were record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 48 publications
0
21
0
1
Order By: Relevance
“…135 However, more recently, experience with DOAC use in patients with Child-Pugh B/C cirrhosis reveals increased bleeding rates in patients with advanced cirrhosis. 136,137 Therefore, caution is required when using DOACs in patients with cirrhosis and further studies are needed.…”
Section: Key Pointmentioning
confidence: 99%
“…135 However, more recently, experience with DOAC use in patients with Child-Pugh B/C cirrhosis reveals increased bleeding rates in patients with advanced cirrhosis. 136,137 Therefore, caution is required when using DOACs in patients with cirrhosis and further studies are needed.…”
Section: Key Pointmentioning
confidence: 99%
“…In patients with Child-Pugh class B, rivaroxaban and edoxaban are contraindicated, while dabigatran and apixaban may be used with caution. In Child-Pugh C patients, direct oral anticoagulants are associated with a high risk of bleeding events 20 and they are contraindicated. 2 Antiplatelet therapies aim to reduce or slow down platelet aggregation, thus precluding thrombus formation.…”
Section: Methodsmentioning
confidence: 99%
“…Several retrospective studies [ 143 , 144 , 145 , 146 , 147 ] and meta-analyses [ 148 , 149 ] have observed a similar or better safety profile in terms of bleeding complications of DOACs compared to VKAs in cirrhotic patients affected by atrial fibrillation, venous thromboembolism, or PVT. Bleeding definitions differed among these studies, and to control for this bias, Nisly et al conducted a systematic review and meta-analysis considering only studies in which the primary safety outcome was major bleeding according to the definition of the International Society on Thrombosis and Haemostasis.…”
Section: Treatmentmentioning
confidence: 99%